2021
DOI: 10.3126/njog.v16i1.37520
|View full text |Cite
|
Sign up to set email alerts
|

Study of Semen Analysis Patterns in Male Partner of Infertile Couple Attending Tertiary Level Hospital of Nepal

Abstract: Aims: The aim of this study is to analyze the pattern of semen abnormality in male partner of infertile couple in Nepal. Methods: A retrospective study of semen sample of male partner of infertile couple analyzed in Department of pathology, Dhulikhel Hospital from January 2014 to December 2018. All semen samples were processed and analyzed according to methods and standards outlined by World Health Organization laboratory manual for the examination and processing of human semen 2010. Results: A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Based on the count, motility and morphology of sperms, half of the samples analyzed had at least one type of abnormality. Abnormality in semen based on the same seminal characteristics was reported to be 44% [22] and 66.2% [18] from two different hospitals of Nepal, which correlates our study with the semen abnormality trend of other studies among the Nepalese population. The most common characteristic in this study was teratozoopermia as with previous studies [14,23].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on the count, motility and morphology of sperms, half of the samples analyzed had at least one type of abnormality. Abnormality in semen based on the same seminal characteristics was reported to be 44% [22] and 66.2% [18] from two different hospitals of Nepal, which correlates our study with the semen abnormality trend of other studies among the Nepalese population. The most common characteristic in this study was teratozoopermia as with previous studies [14,23].…”
Section: Discussionsupporting
confidence: 86%
“…The most common characteristic in this study was teratozoopermia as with previous studies [14,23]. However, asthenozoospermia [22,24], and oligozoospermia [16] were also found to be the most common semen characteristics in Nepal.…”
Section: Discussionsupporting
confidence: 77%
“…5,17,18 Asthenozoospermia followed by azoospermia are the predominant cause for male infertility seen in this study, similar to the findings in other study where asthenozoospermia (39.3%) was the most common abnormality followed by azoospermia (28.8%). 19 A systematic review has by concluded that apart from azoospermia and necrospermia, impaired semen parameters like asthenospermia alone cannot be used to predict fertility as these men still have a chance of being fertile. 20 So treatment options have improved their semen functions.…”
Section: Discussionmentioning
confidence: 99%
“…1,6 World Health Organization also claims 60-80 million couples are facing infertility worldwide. 7,8 In Ethiopia, the burden of infertility is not yet comprehensively studied. 9 The etiologic causes of infertility can be of either the male or the female or both.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 World Health Organization also claims 60–80 million couples are facing infertility worldwide. 7,8 In Ethiopia, the burden of infertility is not yet comprehensively studied. 9…”
Section: Introductionmentioning
confidence: 99%